Labor Market Engagement and the Health of Working Adults: Evidence from India - Archana Dang; Pushkar Maitra; Nidhiya Menon (Institute of Labor Economics (IZA), 2017)
Driven by rapid income growth, labor market transitions in the nature of jobs, and lifestyle factors, there has been a widespread increase in rates of overweight and obesity in many countries. This paper examines the effect of occupational engagement and work intensity on the weight of urban working women and men in India. Using nationally representative data, a variety of specifications that reflect different definitions of work, and empirical methods that correct for the influence of unobservables, we document that labor market inactivity is positively associated with BMI. We offer policy recommendations that may help mitigate some of these unintended consequences. Our paper builds on the fairly limited evidence on the relationship between labor market engagement and health in developing countries.
Keywords: I12; I15; O12; 330; excess weight; labor market; gender; India